Catalytic Enantioselective Synthesis of the Partially Reduced Tricyclic Pyrrolo[3, 2‐c]quinoline Core Structure of the Martinella Alkaloids. Issue 8 (15th June 2016) - Lindbäck, Emil; Sydnes, Magne O.
Abstract: A catalytic enantioselective synthesis of the hexahydropyrrolo[3, 2‐ c ]quinoline core structure found in the Martinella alkaloids, martinelline and martinellic acid, is described. The synthesis is completed without the use of any chiral building blocks or chiral auxiliaries. The key steps in our synthesis constituted a Sp 2 ‐Sp 3 Suzuki‐Miyaura cross‐coupling reaction between a triflate and an N ‐protected β‐aminoethyl boron species to provide a 1, 2‐dihydroquinoline carrying a N ‐protected β‐aminoethyl group in the 3‐position, Sharpless asymmetric dihydroxylation of the 1, 2‐dihydroquinoline derived from the Suzuki‐Miyaura cross‐coupling reaction, and an acid promoted intramolecular diastereoselective amido cyclisation with the aid of a neighbouring acetoxy group to provide the tricyclic architecture of martinelline and martinellic acid. Our catalytic enantioselective synthesis provided the hexahydropyrrolo[3, 2‐ c ]quinoline core structure of the Martinella alkaloids in 75 % ee . Abstract : A catalytic enantioselective synthesis of the hexahydropyrrolo[3, 2‐ c ]quinoline core structure found in the Martinella alkaloids, martinelline and martinellic acid, is described. The synthesis is completed without the use of any chiral building blocks or chiral auxiliaries. The key steps in our synthesis constituted a Sp 2 ‐Sp 3 Suzuki‐Miyaura cross‐coupling reaction, Sharpless asymmetric dihydroxylation, and an acid promoted intramolecular diastereoselective amido cyclisation.